The Impact of Macro-Economic Indicators on Corporate Investment Decisions. A Financial Management Approach - VALIPOUR, Jamal; NAJAFABADIPOUR, Zahra; MOHAMADI, Samira; ZAREEIHEMAT, Pourya; ISAVI, Hero (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025, 2025)
This study investigates the impact of key macroeconomic indicators - including inflation, interest rates, and economic growth - on corporate investment decisions across three major industries: technology, automotive, and energy. Utilizing quarterly data from 2019 to 2024 and applying econometric techniques such as Vector Autoregression (VAR) and Impulse Response Functions (IRFs), the analysis explores how these macroeconomic shocks influence investment behavior. The results reveal that economic growth above the 3% threshold significantly boosts investment in the automotive sector. Conversely, a 1% increase in interest rates leads to a sharp short-term decline in investment within the technology sector, highlighting its sensitivity to monetary tightening. Additionally, the energy sector exhibits a marked reduction in investment levels when inflation exceeds 5%, reflecting the adverse effects of rising input costs and economic uncertainty. These findings underscore the critical role of macroeconomic conditions in shaping investment strategies, particularly in capital-intensive industries.